Analysis of Vina Muliana (@vmuliana)'s Online Identity Formation as a TikTok Influencer : Analisis Pembentukan Identitas Online Vina Muliana (@vmuliana) sebagai Influencer TikTok - Fitrianingsih, Intan; Az Zahra, Amelia Putri; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
In the digital age, social media serves as an important platform for individuals to express themselves and build identities. Vina, who has more than 9.5 million followers, utilizes TikTok to share job search tips, resume building, and interview techniques based on her experience as an HR Senior Associate at a State-Owned Enterprise (SOE). The research method used is a qualitative approach with a case study, analyzing the uploaded content and the interactions that occur on the platform. The results showed that Vina managed to create a positive image through her professional appearance and interactive communication style, while showing her authentic side behind the scenes. Erving Goffman's dramaturgy theory is used as an analytical framework to understand the difference between front stage and back stage in online identity formation. This research provides insight into the role of influencers in shaping identity in the digital era and its impact on audiences. wuThis study aims to analyze Vina Muliana's (@vmuliana) online identity formation as a TikTok influencer who focuses on career education.